Effects of Sex and Breeding Status on Skull Morphology in Cooperatively Breeding Ansell’s Mole-Rats and an Appraisal of Sexual Dimorphism in the Bathyergidae - Caspar, Kai R.; Müller, Jacqueline; Begall, Sabine (Frontiers in Ecology and Evolution, 2021)
African mole-rats of the genus Fukomys (Northern common mole-rats) combine a monogamous mating system and pronounced sexual size dimorphism; a pattern highly untypical for mammals. At the same time, they live in cooperatively breeding groups composed of reproductive and non-reproductive members of both sexes. How and to which degree sex and breeding status influence morphofunctional characters in eusocial mole-rats is not well characterized but essential to come to a comprehensive understanding of their peculiar social system. Here, we explore patterns of morphological differentiation in skulls of Ansell’s mole-rats (Fukomys anselli) by means of multivariate analysis of linear skull measurements combined with a 2D shape analysis of cranium and mandible. Compared to females, males display larger skulls relative to body size and show an expansion of the facial portion of the cranium, while reproductive status did not have an effect on any of the traits studied. We also show that species of Fukomys mole-rats display a scaling of relative sexual body size dimorphism in compliance to Rensch’s rule, which is deemed indicative of intense male intrasexual competition. For the bathyergid family as a whole, results of scaling analyses were more ambiguous, but also indicative of Rensch’s rule conformity. In line with genetic field data, our results point to a greater role of male-male conflicts in Fukomys than is traditionally assumed and support the notion that reproductive status does not correlate with morphofunctional segregation in these unusual rodents.